Study on the effect of membrane electrode assembly parameters on polymer electrolyte membrane fuel cell performance by galvanostatic charging method. (1st October 2019) - Wu, Ziyao; Pei, Pucheng; Xu, Huachi; Jia, Xiaoning; Ren, Peng; Wang, Bozheng
Highlights: A decrease of resistance due to clamping is a key factor of a cell performance boost. Hydrogen pump increases the water content of membrane and active sites of catalyst. The voltage of fuel cell at low current can be calculated by electrode parameters. Rising ohmic resistance has the biggest effect on the early performance of fuel cell. The catalysts deactivation is the primary factor of fuel cell aging after 150 cycles. Abstract: The membrane electrode assembly (MEA) is one of the essential components of the polymer electrolyte membrane fuel cell. Its quality and state greatly influence the fuel cell performance, which can be characterized by MEA parameters, including ohmic resistance, hydrogen crossover current, double layer capacitance, and catalyst roughness factor. These parameters of a single cell or multiple cells in a stack can be detected simultaneously by the galvanostatic charging method. In this paper, this method was used to test two 34 cm 2 single cells and one 300 cm 2 four-cell stack during assembly, activation and aging, respectively, in order to investigate variations of MEA parameters and their effects on the fuel cell performance. With the assembly torque increasing, the decrease of ohmic resistance makes major contribution to the performance improvement of a fuel cell. With repeating hydrogen pump activation, the increase of active sites and the decrease of the ohmic resistance improve the fuel cell performance gradually. Simultaneously, the logarithmic relationship between the Tafel coefficients and the catalyst roughness factor is observed, based on which a functional expression for calculating the fuel cell performance only by MEA parameters is established. As for the accelerated aging test, the increase of ohmic resistance exerts a significant influence on the performance of a stack in the initial stage, but it only results in a 10% performance degradation after 200 aging cycles. Actually, the decrease of the catalyst roughness factor affects the stack performance primarily.